EMPLOYEE PAYROLL SYSTEM DESIGN USING EXTREME PROGRAMMING ALGORITHM - Muhammad Luthfi Hamzah; Daffa Takratama Savra; Della Harmutika; Rahma Sani Nahampun; Ali Alamuddin Muzaffar; Anjasy Syahroni; Abdul Hamid (Jurnal Testing dan Implementasi Sistem Informasi, 2025)
The employee payroll system was built to make it easier for companies, especially those that still handle payroll manually, to manage employee payroll data. Company X still records employee information, absence information, and salary information manually in a book as part of its employee payroll process. The design of the employee payroll system in this study uses the Extreme Programming method. The Extreme Programming approach is used in the design of the employee payroll system in this study. This study also tests the system. The system is tested using White-box and Black-box testing methodologies, with the aim of testing the functional and non-functional requirements of the system. The findings of this study lead to the creation of an employee payroll information system that Company X can use to facilitate the payroll process for its employees.